PERANAN HUMAN RELATIONS DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR KECAMATAN WORI KABUPATEN MINAHASA UTARA - Rondonuwu, Sintje (JURNAL ADMINISTRASI PUBLIK, 2014)
Abstract: Human relations is an important aspect to succeed personal or group communication.Human relations is also the part of the leader or manager in an organization, because the leaderalmost spent every day doing lot of communication vertically and horizontall y. Human relationactivity can be done in every situation occurred in every aspect of life. Human relation alsoaffect the opinion, behavior and attitude. Human relation is important to increase organizationalperformance especially the servant performance.Kata kunci: Human Relations, Performance